STAVUDINE LOADED BIODEGRADABLE POLYMERIC MICROSPHERES AS A DEPOT SYSTEM FOR PARENTERAL DELIVERY (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
Injectable biodegradable polymeric microspheres of Stavudine were prepared using different viscosity grades of PLGA 50:50 (RESOMER® 504H and RESOMER® 502H) by solvent evaporation technique with different drug/polymer ratios. Tailored release of Stavudine facilitates reduction in symptoms of HIV infection and delay AIDS progression by reducing viral load to undetectable levels for extended period of time. The influence of formulation variables on microparticle characteristics like polymer type and concentration, vehicle type, polymer solution/vehicle volume ratio, surfactant concentration and drug to polymer ratios were evaluated. Microspheres were evaluated for yield, entrapment efficiency, particle size and in-vitro release behavior as well as characterized by scanning electron microscopy (SEM), differential scanning calorimetry (DSC), X-ray diffraction (XRD), residual solvent analysis and confocal laser scanning microscopy (CLSM). Microspheres showed excellent surface topography with uniform distribution and structural integrity of the drug having the entrapment efficiency of 90.96 ± 1.09 and mean particle diameter below 65μm. Drug release kinetics data were obtained from various kinetic models and best explained by “Korsmeyer-Peppas equation” for both the polymers which depicted that drug release mechanism is anomalous transport, i.e. diffusion as well as polymer relaxation. Drug release from microspheres exhibited the characteristic release pattern of a monolithic matrix system with 90-100% drug release in 6-8 weeks demonstrating the feasibility of prolonged delivery of Stavudine using biodegradable microspheres for parenteral depot system.